On the setwise convergence of sequences of measures. (1997) - Lasserre, Jean B.
Abstract : We consider a sequence μ n of (nonnegative) measures on a general measurable space ( X, ℬ ) . We establish sufficient conditions for setwise convergence and convergence in total variation.